О синономике наименований циклопов (Crustacea, Cyclopidae) в работах некоторых отечественных зоологов XIX века - Монченко, В.И. (Вестник зоологии, 1973)
To save the stability of zoological nomenclature the newly, discovered senior synonyms Cyclops harpacticoides S h m a n k e v i c h, 1875 for Halicyclops neglectus neglectus K i e f., 1935 and Cyclops orientalis U l j a n i n, 1875 for Microcyclops (s. str.) varicans rubellus (L i l l., 1901) in the author's opinion, must not replace the tradition denominations. Another Shmankevich (1875) descriptions are identified for the first time: Cyclops minutus varietal —with Microcyclops (s. str.) varicans varicans (S a r s), Cyclops brevicornis varietas (C. vinceus sp. n.) — with Acanthocyclops (s. str.) vernalis (F i s c h.) (s. lat.), Cyclops brevicaudatus var. a — with C. strenuus Fisch. (s. lat.), C. brevicaudatus var. b — with C. furcifer C l a u s, C. bicuspidatus varietas and C. odessanus varietas— with Diacyclops bicuspidatus bicuspidatus (C l a u s). Another Uljanin (1875) descriptions are identified for the first time: C. signatus Koch text part — with Macrocyclops fuscus (J u r.), drawing part — with M. albidus (J u r.), Cyclops viridis J u r. — with Acanthocyclops (Megacyclops) gigas (C l a u s). Cyclops fedtschenkoi sp. n. and C. sarsi sp. n. are considered as species incertae sedis. Some Sowinski (1887, 1887a, 1888) descriptions are indentified for the first time: Cyclops uljanini sp. n.— with C. vicinus vicinus U l j., C. kievensis sp. n.— with Diacyclops bisetosus (R e h b.), Cyclops hamatus sp. n. with C. furcifer (C l a u s), C. korostyschevi sp. n. — with Macrocyclops fuscus (J u r.), Cyclops diaphanus Fisch. — with Microcyclops (Cryptocyclops) bicolor (Sars), Cyclops longicaudatus ,Poggenpol—with Mesocyclops leuckarti (C l a u s), Cyclops helleri Brady—with Acanthocyclops (M.) (J u r.), Cyclops clausi var. bidens var. n. and C. intermedius sp. n. are considered as nominae nuda.